β-Carotene in Golden Rice is as good as β-carotene in oil at providing vitamin A to children - Tang, Guangwen; Hu, Yuming; Yin, Shi-an; Wang, Yin; Dallal, Gerard E; Grusak, Michael A; Russell, Robert M (The American journal of clinical nutrition, 2012)
Background: Golden Rice (GR) has been genetically engineered to be rich in β-carotene for use as a source of vitamin A.Objective: The objective was to compare the vitamin A value of β-carotene in GR and in spinach with that of pure β-carotene in oil when consumed by children.Design: Children (n = 68; age 6–8 y) were randomly assigned to consume GR or spinach (both grown in a nutrient solution containing 23 atom% 2H2O) or [2H8]β-carotene in an oil capsule. The GR and spinach β-carotene were enriched with deuterium (2H) with the highest abundance molecular mass (M) at Mβ-C+2H10. [13C10]Retinyl acetate in an oil capsule was administered as a reference dose. Serum samples collected from subjects were analyzed by using gas chromatography electron-capture negative chemical ionization mass spectrometry for the enrichments of labeled retinol: Mretinol+4 (from [2H8]β-carotene in oil), Mretinol+5 (from GR or spinach [2H10]β-carotene), and Mretinol+10 (from [13C10]retinyl acetate).Results: Using the response to the dose of [13C10]retinyl acetate (0.5 mg) as a reference, our results (with the use of AUC of molar enrichment at days 1, 3, 7, 14, and 21 after the labeled doses) showed that the conversions of pure β-carotene (0.5 mg), GR β-carotene (0.6 mg), and spinach β-carotene (1.4 mg) to retinol were 2.0, 2.3, and 7.5 to 1 by weight, respectively.Conclusions: The β-carotene in GR is as effective as pure β-carotene in oil and better than that in spinach at providing vitamin A to children. A bowl of ∼100 to 150 g cooked GR (50 g dry weight) can provide ∼60% of the Chinese Recommended Nutrient Intake of vitamin A for 6–8-y-old children. This trial was registered at www.clinicaltrials.gov as NCT00680212.